Quantum chemical calculations of 31P NMR chemical shifts of P-donor ligands in platinum(II) complexes - Sojka, Martin; Nečas, Marek; Toušek, Jaromir (Journal of molecular modeling, 2019)
This work aims to find the most suitable method that is practically applicable for the calculation of 31P NMR chemical shifts of Pt(II) complexes. The influence of various all-electron and ECP basis sets, DFT functionals, and solvent effects on the optimized geometry was tested. A variety of combinations of DFT functionals BP86, B3LYP, PBE0, TPSSh, CAM-B3LYP, and ωB97XD with all-electron basis sets 6-31G, 6-31G(d), 6-31G(d,p), 6-311G(d,p), and TZVP and ECP basis sets SDD, LanL2DZ, and CEP-31G were used. Chemical shielding constants were then calculated using BP86, PBE0, and B3LYP functionals in combination with the TZ2P basis. The magnitude of spin-orbit interactions was also evaluated.
Keywords: Spin-orbit interactions; DFT calculations; 31P NMR; Pt complexes